A Risk Diagnosing Methodology Web-Based Platform for Micro, Small and Medium Businesses: Remarks and Enhancements - Pereira, Luís; Tenera, Alexandra; Bispo, João; Wemans, João (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
The indisputable necessity to innovate brings to companies vital responsibilities such as the inevitable errand of having consistent innovation and risk management procedures along their projects. This work presents a risk diagnosing methodology (RDM) web-platform, that can provide to Small and Medium Enterprises (SMEs) the ability to identify and self-assess risks associated with their innovative project’s portfolio, from the project’s idealization to its commercialization. The creation of this tool attempts to encourage SMEs on the systematic use of risk management approaches, in order to increase project’s successful rates. As groundwork, this paper also includes a bibliographical review and comparative analysis of other existing risk management tools and models available to SMEs. The present article also uncovers first empirical results available from exploratory research done and reveals ongoing research efforts regarding risk perception and potential bias correction.